Fever of Unknown Origin as a Sole Presentation of Subacute Thyroiditis in an Elderly Patient: A Case Report with Literature Review - Rishi Raj; Srujana Yada; Aasems Jacob; Dileep Unnikrishnan; Wael Ghali (Case Reports in Endocrinology)
An 80-year-old Caucasian male presented with fever of 3-week duration. Outpatient workup for infectious etiologies was negative and due to persistent fever, he was hospitalized for further evaluation of fever of unknown origin (FUO). Physical examination and laboratory studies remained unremarkable; however a follow-up CT scan of chest, abdomen, and pelvis with contrast done to rule out malignancy as an underlying cause of FUO revealed heterogeneous thyroid gland with surrounding hazy changes suggestive of thyroiditis. Thyroid function tests confirmed the diagnosis of subacute thyroiditis. The patient was started on prednisone with good response in his symptoms and was eventually discharged to home. The importance of our case lies in the fact that diagnosing subacute thyroiditis in the absence of classical symptoms of neck pain can be challenging and a physician should have a very high index of suspicion especially in an elderly patient where FUO can be the sole presentation.